2023
DOI: 10.1155/2023/4308517
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors of Self-Management Behavior among Chinese Stroke Patients

Abstract: Background. Stroke is associated with a high number of disability-adjusted life years globally, so long-term care is necessary and important for those survivors, so self-management is becoming a more significant concept in stroke rehabilitation. Methods. Ischemic stroke patients (n = 354) were enrolled from the outpatient department of Neurology in West China Hospital from September 2018 to December 2019. The general demographic and disease-related data of stroke patients were collected. The stroke self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Regarding the factors associated with preferences for PHC, our research reveals that homebound patients, who had received inpatient care in the past year, in both rural and urban areas, were less likely to opt for PHC. Homebound patients tend to prefer higher-level hospitals with more medical resources, likely due to poor post-discharge self-management behavior and inadequate monitoring after discharge [ 34 35 ], resulting in serious health problems, as evidenced by previous studies [ 34 35 ]. This finding has significant implications for clinical and policy practices.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the factors associated with preferences for PHC, our research reveals that homebound patients, who had received inpatient care in the past year, in both rural and urban areas, were less likely to opt for PHC. Homebound patients tend to prefer higher-level hospitals with more medical resources, likely due to poor post-discharge self-management behavior and inadequate monitoring after discharge [ 34 35 ], resulting in serious health problems, as evidenced by previous studies [ 34 35 ]. This finding has significant implications for clinical and policy practices.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of SM in kidney transplant patients, researchers found that SM increased with age (Xie et al, 2019 ). In addition, one study in China found that the SM of stroke patients tended to improve with age (Shuqi et al, 2023 ). Therefore, compared with the previous studies in China, the higher SM score in this study might be due to differences in the ages of the sample population.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, there is a growing tendency for stroke to occur at younger ages, as approximately 30%-50% of all patients with stroke are under 65 years old (Ren et al 2020). The results of the present Owing to the concurrent demands of employment and familial obligations among their peers, the youthful demographic has challenges in committing to extended rehabilitation (Shuqi et al 2023). As young individuals with longevity and life expectancy following a stroke may consider returning to society more, adult patients have better selfmanagement than older ones.…”
Section: Correlation Between Individual-related Factors and Self-mana...mentioning
confidence: 99%
“…This behavior consequently poses a heightened risk of experiencing subsequent strokes. The inadequate self-management behavior exhibited by patients with stroke can be attributed to several factors, including individual-related factors, such as age, gender, and residence (Shuqi et al 2023;Sun et al 2022), and health service provider factors, including limited information availability, restricted access to healthcare services, inadequate availability of health facilities (Harfika and Abdullah 2017), and suboptimal collaboration among healthcare professionals (Busari, Moll, and Duits 2017). Health services is defined by the World Health Organization (WHO) as "service delivery systems that are accountable for providing health services to patients, individuals, families, communities, and populations in general, not just patients" (WHO 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation